Transformasi Kurikulum Indonesia: Adaptasi Kebijakan Pendidikan di Era Globalisasi Melalui Kurikulum Merdeka dan Integrasi Deep Learning - Laila Fathimah; Muhammad Sofwan; Ilham Putra Pratama; Siti Halimah (Tarbiatuna: Journal of Islamic Education Studies, 2025)
Curriculum policy in Indonesia continues to transform dynamically in response to the challenges of globalization and the demands of internal reform. This study aims to analyze the evolution of national curriculum policy in the post-reform era and examine the implementation of the Kurikulum Merdeka (Independent Curriculum) as well as the integration of Deep Learning as adaptive strategies for addressing the complexities of the 21st century. Utilizing a literature review method, this research synthesizes data from laws and regulations, government policy documents, and various relevant scientific articles. The analysis reveals that the evolution of the curriculum from the Competency-Based Curriculum (KBK) of 2004 to the Kurikulum Merdeka represents a logical journey from a centralized paradigm to full decentralization and autonomy. The Kurikulum Merdeka, grounded in the philosophies of humanism, social constructivism, and local wisdom, emerges as a response to the need for more personalized and contextual learning. Furthermore, the integration of Deep Learning through content development, technology-based projects, and industry collaboration is identified as a strategic step in equipping students with digital competencies relevant to the Fourth Industrial Revolution. It is concluded that this adaptive curriculum policy has significant potential to enhance national competitiveness; however, its success heavily relies on the education system's ability to overcome fundamental challenges such as equitable infrastructure quality and the continuous improvement of teacher capacity.